Conservative management of early uncomplicated appendicitis in children - Maini, Sunil Kumar; Jain, Neeraj Kumar; Jain, Manjari Goel; Khobragade, Vicky (International Surgery Journal, 2017)
Background: Right lower abdominal pain management in children is a challenging task for the surgeon. Most of the time right lower abdominal pain ends up in acute appendicitis. For long time appendicetomy was the treatment of choice. However surgical intervention has its own disadvantages such as pain, scarring, adhesions, hernia development and venous thrombosis disease. Anxiety and fear of surgery were also two difficulties in obtaining consent for surgery. Parents often request and insist for medical management. Their unwillingness for surgical intervention was the most important reason for medical management of uncomplicated acute appendicitis. Methods: Our prospective observational study was conducted in the Department of General Surgery, R.K.D.F. Medical College and Research Centre, Bhopal, Madhya Pradesh, India during period of January 2014 to January 2016 and follow up was done till December 2016. Our target group was children under 16 years. A total of 92 children with complaint of right lower abdominal pain attended the hospital for treatment. Routine investigations including ultrasonography of abdomen were performed for all the patients. Out of 92 patients diagnosis of acute appendicitis was made in 74 patients, Surgery was performed in 32 patients, while remaining 42 patients were treated conservatively and the results were analyzed. Results: In this study of 92 patients of pain in right iliac fossa below 16 years, 74 (80.43%) were diagnosed as acute appendicitis. 32 (43.24%) Patients were operated earlier. 42 (56.75%) Patient were treated conservatively. Out of 42 patients, 12 (16.21%) patients were operated within 1 year, 30 (40.54%) Patients didn’t require any surgical intervention during 1 year follow up. In present study, significant role of antibiotic was found in conservative management of acute appendicitis in children. So it can be concluded that conservative management of acute appendicitis in children can be attempted under observation. Conclusions: Antibiotics are both effective and safe as primary treatment for patients with uncomplicated acute appendicitis. Initial antibiotic treatment merits consideration as a primary treatment option for early uncomplicated appendicitis. Appendicectomy should be done but conservative management of acute appendicitis in children can be attempted under observation.